The Effect of Ethical Knowledge, Religiosity and Moral Reasoning on Accounting Student's Perception of Creative Accounting Practices - Pratiwi, Dhika Ayu; Fajar, Muhammad Andryzal (Universitas Negeri Yogyakarta, 2023)
ABSTRACTThis study aims to knows the effect of ethical knowledge, religiosity and moral reasoning on the accounting student's perception of creative accounting practices. The population uses accounting students of Yogyakarta State University (UNY) and Universitas Muhammadiyah Yogyakarta (UMY). The sample were 147 respondents. Data analysis is based on multiple linear regression analysis. The results showed that ethical knowledge positively influences the perception of accounting students regarding creative accounting practices, religiosity does not affect the perception of accounting students regarding creative accounting practices and moral reasoning has a positive effect on accounting students' perceptions about creative accounting practices. Additional testing for different test show ethical knowledge has significant different whereas religiosity and moral reasoning no significant different between accounting student's UNY and UMY.Keywords: Knowledge of Ethics, Religiosity, Moral Reasoning, Creative Accounting PracticesABSTRAKPenelitian ini bertujuan mengetahui pengaruh pengetahuan etika, religiusitas dan moral reasoning terhadap persepsi mahasiswa akuntansi mengenai praktik creative accounting. Populasi menggunakan mahasiswa Prodi Akuntansi Universitas Negeri Yogyakarta (UNY) dan Universitas Muhammadiyah Yogyakarta (UMY). Sampel sebesar 147 responden. Analisis data menggunakan analisis regresi linear berganda. Hasil penelitian menunjukkan pengetahuan dan etika berpengaruh positif terhadap Persepsi mahasiswa akuntansi mengenai praktik creative accounting, Religiusitas tidak berpengaruh terhadap persepsi mahasiswa akuntansi mengenai praktik creative accounting dan moral reasoning berpengaruh positif terhadap Persepsi mahasiswa akuntansi mengenai praktik creative accounting. Tes tambahan untuk uji beda menunjukkan pengetahuan etika mempunyai perbedaan signifikan sedangkan religiusity dan moral Reasoning tidak mempunyai perbedaan signifikan antara mahasiswa prodi akuntansi di UNY dan UMY.Kata Kunci: Pengetahuan Etika, Religiusitas, Moral Reasoning Praktik, Akuntansi Kreatif